Does immigration raise natives' income? National and regional evidence from Spain - Catalina Amuedo-Dorantes; Sara de la Rica (Institute for the Study of Labor (IZA), 2008)
How immigration affects the labor market of the host country is a topic of major concern for many immigrant-receiving nations. Spain is no exception following the rapid increase in immigrant flows experienced over the past decade. We assess the impact of immigration on Spanish natives' income by estimating the net immigration surplus accruing at the national level and at high immigrant-receiving regions while taking into account the imperfect substitutability of immigrant and native labor. Specifically, using information on the occupational densities of immigrants and natives of different skill levels, we develop a mapping of immigrant-to-native self-reported skills that reveals the combination of natives across skills that would be equivalent to an immigrant of a given self-reported skill level, which we use to account for any differences between immigrant self-reported skill levels and their effective skills according to the Spanish labor market. We find that the immigrant surplus amounts to 0.04 percent of GDP at the national level and it is even higher for some of the main immigrant-receiving regions, such as Catalu\~na, Valencia, Madrid, and Murcia.
urn:nbn:de:101:1-2008052761
Keywords: J61; 330; International migration; regional; national; immigration surplus; Spain; Einwanderung; Qualifikation; Einkommen; Internationale Arbeitsmobilität; Region; Makroökonomischer Einfluss; Spanien